Profiling consumers based on information use and trust in a developing economy - Collins Asante-Addo; Daniela Weible (International Journal of Consumer Studies, 2020)
In the wake of the intense debate about the effect of poultry imports on domestic poultry industries in sub-Saharan Africa, information campaigns have evolved to encourage the consumption of domestic poultry meat products. Nevertheless, consumers use numerous channels to find information, and thus, the extent to which resources should be allocated to these channels to reach segments of consumers is vital. The purpose of this paper is to identify consumer groups based on use and trust in information sources and then profile the segments using sociodemographic variables, purchase motives, and meat consumption. Face-to-face interviews were used to collect data amongst 500 urban consumers in Ghana, which were analysed with factor analysis and two-step cluster analysis. Results show that consumers frequently use personal sources of information about chicken. Cluster analysis revealed three consumer segments: cautious consumers (18.2%), enthusiastic consumers (53.0%), and optimistic consumers (28.8%). The segments differed significantly regarding the type of information searched for, sociodemographic characteristics, purchase motives, and chicken meat consumption patterns. The findings can aid actors and institutions seeking to increase the consumption of domestic poultry meat in developing targeted communication strategies that suit the characteristics, motivations, and information needs of different consumers.
Keywords: 330; cluster analysis; consumer segmentation; factor analysis; information sources; motives; poultry meat; trust